The constituents, ideas, and trends in team-based learning: a bibliometric analysis - Flores-Cohaila, Javier A.; Moreno Ccama, Vanessa Patricia; Baca Quispe, Aitana Libertad; Lopez Ayquipa, Alisson Micaela; Paz Gamarra, Francesca Alessandra; Alfaro Peña, Pierre Valentino; Copaja-Corzo, Cesar (Frontiers in Education, 2024)
Team-based learning (TBL) has gained significant popularity in higher education. Despite its widespread adoption, there is a lack of comprehensive understanding of the current state of TBL research. Hence, we conducted a bibliometric analysis to address this gap, reviewing 692 papers from the Web of Science database. The study revealed a notable increase in TBL research, with a peak of 87 publications in 2021. The United States emerged as the leading contributor, with medical and nursing education being the most prominent research areas. Specialized journals played a significant role in disseminating TBL research. Key themes, including TBL outcomes, non-technical competencies, and implementation principles, were identified. Moreover, it highlighted a growing interest in applying TBL in interprofessional education and formative assessment. The findings suggest the need to establish priorities and expand TBL research beyond health professions education to other fields. This study provides valuable insights into the current landscape of TBL research and offers directions for future investigations.